Evaluation of the Single‐Use Fixed‐Bed Bioreactors in Scalable Virus Production. Issue 1 (12th October 2020) - Lesch, Hanna P.; Valonen, Piia; Karhinen, Minna
Abstract: The accelerating development of gene therapy from research towards clinical trials and beyond has elevated the demand for practical viral vector‐manufacturing solutions. The use of disposable upstream technology is gaining traction in clinical manufacturing. Packed‐bed or fixed‐bed reactors, where column is packed with immobilized biocatalyst particles providing surface to constrain the cells in a particular region of the reactor, have been widely used in bioprocessing applications since mid‐1900s. However, the world's first single‐use, fully integrated, high cell density, fixed‐bed bioreactor was launched only approximately a decade ago. By now, several single‐use, fixed‐bed technology solutions have been developed in a small scale. Scaling‐up the manufacturing can be challenging and for commercial‐scale manufacturing, there is practically only one single‐use, good manufacturing practice‐compliant option available. This study reviews the latest, fully disposable, fixed‐bed bioreactors; compares the virus production in the different systems; and discusses important manufacturing cost‐related topics. It is predicted that single‐use, fixed‐bed bioreactors will receive even more attention in the field of viral vector manufacturing and commercialization, especially with the need for higher virus titers and virus yields. Abstract : Adherent cells can attach and grow in three‐dimensional fixed‐bed matrix. The single use disposable upstream technology has been implemented in many different viral vector and vaccine productions. Main process steps in viral production contain cell expansion phase, induction of the virus production and harvest.